Facemask Wearing Among Chinese International Students From Hong Kong Studying in United Kingdom Universities During COVID-19: A Mixed Method Study - Lai, Agnes Yuen-kwan; Sit, Shirley Man-man; Lai, Theresa Tze-kwan; Wang, Man-ping; Kong, Cecilia Hoi-mei; Cheuk, Jessica Yuet-ying; Feng, Yibin; Ip, Mary Sau-man; Lam, Tai-hing (Frontiers in Psychiatry, 2021)
Background: The mental health of international students studying abroad has been neglected during the COVID-19 pandemic. Objective: This mixed-method study examined perceived public attitudes, personal beliefs, practice and stress toward facemask wearing as a preventive measure against COVID-19 among international University students from Hong Kong studying in the United Kingdom (UK) in the early stage (January–March 2020) of the pandemic. Methods: Our study included 2 parts: (i) an exponential, non-discriminative snowball sampling strategy was used to recruit 91 Chinese students studying in the UK to complete an online questionnaire survey, and (ii) online Zoom focus group interviews were conducted with 16 students who completed the online survey to gain an in-depth understanding of their experiences and coping methods during the pandemic. Results: Of the 91 students, 92.3% reported the UK public did not view facemask wearing as a preventive measure. 98.9% believed facemask wearing was an effective preventive measure, but 56% wore facemasks more than half of the time when out in public. 50.5% had internal conflicts of stress both when wearing and not wearing facemasks, which was more common in females than males [(62.5 vs. 31.5%), P = 0.004, Relative Risk (RR): 1.99 (1.17, 3.38)]. 61.5% reported public prejudiced attitudes against facemask wearing, also more common in females than males (71.4 vs. 45.7%), P = 0.02, RR: 1.56 (1.05, 2.32). The qualitative findings corroborated with the quantitative findings and reported that peer and family support were important for them to face such difficulties, and positive thinking and adaptability were effective methods on stress management. Conclusions: Since the outbreak of COVID-19, Chinese international students have been faced with a difficult, confusing, and sensitive situation. Owing to the ongoing pandemic, rising xenophobia and racist behaviors and the resumption of students' studies studies in the U.K., support from global communities are needed in their pursuit of quality education overseas. Our findings have significant implications on the proactive roles that governments should have, and the need for clear and accurate public health messaging to change public attitudes and mitigate prejudice. Academic institutions and mental health professionals need to proactively provide additional support to Chinese international students.